2001
DOI: 10.1021/jp011750d
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of the Quaternary Poly(dl-lactide-co-glycolide)/Monoolein/1-Methyl-2-pyrrolidinone/Water System:  An Experimental and Theoretical Study

Abstract: The phase behavior of the poly(dl-lactide-co-glycolide) (PLG)/monoolein (MO)/1-methyl-2-pyrrolidinone (NMP)/water system has been studied. The particular system was selected because it was a candidate for being a suitable system for creation of lipid−polymer hybrid particles. Phase diagrams of the four ternary subsystems, as well as phase behaviors of selected quaternary mixtures, have been determined. The PLG/NMP/water system exhibits a behavior similar to a polymer/solvent/nonsolvent system, and the PLG/MO/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In situ forming depot systems appeared in the field of controlled drug release as an alternative to microspheres in order to overcome the disadvantages noticed for microspheres such as the need of reconstitution, the possibility of microsphere migration after injection, and high fabrication cost, low encapsulation efficiency for some APIs (87)(88)(89)(90). These in situ forming depot systems generally are injectable polymer or lipid solutions/suspensions having low viscosity before injection, and solidify into semi-solid or solid depots after administration into the body (91).…”
Section: In Situ Forming Depot Systemsmentioning
confidence: 99%
“…In situ forming depot systems appeared in the field of controlled drug release as an alternative to microspheres in order to overcome the disadvantages noticed for microspheres such as the need of reconstitution, the possibility of microsphere migration after injection, and high fabrication cost, low encapsulation efficiency for some APIs (87)(88)(89)(90). These in situ forming depot systems generally are injectable polymer or lipid solutions/suspensions having low viscosity before injection, and solidify into semi-solid or solid depots after administration into the body (91).…”
Section: In Situ Forming Depot Systemsmentioning
confidence: 99%
“…It will be demonstrated that the phase behavior, of the system used for the encapsulation process, is of main importance, in particular when particles are created by a slow process such as emulsification. At least one other quaternary system containing a biocompatible solvent (1-methyl-2-pyrrolidinone) has been explored before . The system reported in ref is of general interest even though emulsification in aqueous solution is practically unworkable due to the instantaneous diffusion of NMP out to the water phase.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The technical grade has been used as an emulsifying agent and a food additive since the 1950s, and it has also been utilized as a coamphiphile in pharmaceutical applications. 24 The liquid crystalline structures formed by MO have been proposed to be utilized as alternatives to lipid vesicles for administration of drugs, providing slow release [25][26][27][28] and stabilization of sensitive substances. 27,[29][30][31] Another potentially interesting application for these compounds is the use of them in electrochemical biosensors based on enzymes entrapped in a cubic phase.…”
Section: Introductionmentioning
confidence: 99%
“…36 To fully utilize these applications, several aspects must be thoroughly studied and a detailed knowledge of the phase behavior must be obtained. Several more or less complete ternary systems involving MO can be found in the literature, and they may contain from small-and medium-sized molecules and ions [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] to polymers 28,53,54 and proteins. [29][30][31][32][55][56][57][58][59] Generally, inorganic ions 37 and small molecules such as urea 37 and sugars 37,38,46 can be incorporated in substantial amounts (mol/L) into the cubic phases without causing major structural changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation